Politician's dilemma : building state capacity in Latin America - Geddes, Barbara (California series on social choice and political economy ;, 1994)
In Latin America as elsewhere, politicians routinely face a painful dilemma: whether to use state resources for national purposes, especially those that foster economic development, or to channel resources to people and projects that will help insure political survival and reelection. While politicians may believe that a competent state bureaucracy is intrinsic to the national good, political realities invariably tempt leaders to reward powerful clients and constituents, undermining long-term competence. Politician's Dilemma explores the ways in which political actors deal with these contradictory pressures and asks the question: when will leaders support reforms that increase state capacity and that establish a more meritocratic and technically competent bureaucracy? Barbara Geddes brings rational choice theory to her study of Brazil between 1930 and 1964 and shows how state agencies are made more effective when they are protected from partisan pressures and operate through merit-based recruitment and promotion strategies. Looking at administrative reform movements in other Latin American democracies, she traces the incentives offered politicians to either help or hinder the process. In its balanced insight, wealth of detail, and analytical rigor, Politician's Dilemma provides a powerful key to understanding the conflicts inherent in Latin American politics, and to unlocking possibilities for real political change.